CRIMINAL ENFORCEMENT FOR CHILDREN IN PROGRESSIVE STUDIES - Hardanti Widya Khasna (IJCLS (Indonesian Journal of Criminal Law Studies), 2018)
This research has a purpose to know how exactly the implementation of crime against children under age that occurred in Indonesia, viewed from the of progressive law. The method of research used in this research is qualitative method with normative juridical approach. In this research can be determinated the result that in the enforcement of crime for children under age, the process is different with criminal law enforcement in general. From the settlement of the case as soon as possible, the investigator must be a child-specific investigator, the child's examination is conducted in a familial atmosphere, and the investigator is required to seek advice from the Counselor. This is in accordance with what has been mandated in Law Number 35 Year 2014 on the Amendment of Law Number 23 Year 2002 on Child Protection. In the future wish that society and goverment understand the meaning of real justice, that in the child crime, there is a value that need to be prioritised called restorative justice.